Invisibility Cloak with Use of Nonsingular Coordinate Transformation - V.I. Vyunnik; A.A. Zvyagintsev (Журнал нано- та електронної фізики)
The non-singular coordinate transformation is investigated; the expressions for the components of permittivity and permeability are obtained. Numerical modelling of the corresponding object of invisibility was performed. A comparison of the total value of the scattering from nonsingular and singular invisible object was completed. It was shown that the total amount of scattering from an invisible object in the far zone corresponds to the scattering from perfectly conducting cylinder, which is the “base” of the coordinate transformation.